Multivalued generalizations of fixed point results in fuzzy metric spaces - Došenovic, Tatjana; Rakic, Dušan; Caric, Biljana; Radenovic, Stojan (Nonlinear Analysis: Modelling and Control, 2016)
This paper attempts to prove fixed and coincidence point results in fuzzy metric space using multivalued mappings. Altering distance function and multivalued strong bn-fuzzy contraction are used in order to do that. Presented theorems are generalization of some well known single valued results. Two examples are given to support the theoretical results.